2D ANIMATION CREATION WITH BUJANG GANONG ART THEME - Anindhitya, Hanung; Rachman, Anung; Kurniawan, Rendya Adi (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2022)
In this day and age, many traditional arts are marginalized. Marginalization according to the Big Indonesian Dictionary can be interpreted as